The demobilization within mobilization. Reflections based on Pablo work "Transgenic Argentina. From resilience to adaptation, an ethnography of peasant populations" - Quintana Thea, Abril (2024)
One of the major questions faced by researchers analyzing social movements and collective action revolves around determining what happens when a social movement fails to develop, sustain over time, or even establish itself. This phenomenon is often seen as a negative process, characterized by apathy and absence of resources or political opportunities. This question remains relatively unexplored in academic circles dedicated to the study of social movements, prompting Lapegna in his book Transgenic Argentina. From resilience to adaptation, an ethnography of peasant populations, to revisit the analysis of demobilization. The author starts from the premise that this is a process and mechanism involving decision-making and activity, challenging theories that characterize it negatively. Lapegna ethnographically analyzes a case in Moreno (Formosa, Argentina), where the soy boom and the use of agrochemicals affect the entire peasant population. He observes how in 2003, faced with agrochemical drift, the community organizes demonstrations and manages to stop the spraying of neighboring fields. However, in 2009, facing the same situation, the same population does not undertake any collective action. From there, the author seeks to deepen the study of the relationship between clientelistic policies and social movements to explain the process of demobilization.